Expanding family planning options: offering the Standard Days Method™ to women in Istanbul. Issue 2 (1st April 2005) - Kalaca, Sibel; Cebeci, Dilsad; Cali, Sanda; Karavus, Melda; Sinai, Irit; Jennings, Victoria
Abstract : Background: This study introduced the Standard Days Method™ (SDM), a fertility awareness-based method of family planning, to couples in a region of Istanbul, Turkey who were using a method of low effectiveness or no family planning method. The objective was to determine potential demand for, and satisfaction with, the SDM. Methods: A total of 657 couples were selected by systematic sampling and offered the SDM. Those accepting this method were interviewed 1 and 3 months after starting the SDM. Results: Some 47% of the participants were satisfied with the method and intended to continue using it. Conclusions: Potential demand for the SDM was 80.3% (278/346 eligible women) among couples who were using a method of low effectiveness or no family planning method. Our results suggest that adding the SDM to the contraceptive method mix may benefit Turkish women.